(untitled) (Global Journal of Human-Social Science, 2021)
This article is based on the proposal to discuss the mental health of the homeless population, from bibliographic researches of authors from related areas, such as psychology and psychoanalysis, taking as a starting point the current socioeconomic model and its consequences on the social and psychic spheres of the subjects, briefly going through the establishment of brazilian public policies, as well as the dismantling that the mental health field has been suffering over the past few years by the governmental administrations. This production is proposed to serve as an enrichment tool for the literature, as a way to further the discussion of the developed contents.